2008
DOI: 10.1061/(asce)0893-1321(2008)21:4(280)
|View full text |Cite
|
Sign up to set email alerts
|

Wind Environmental Conditions in Passages between Two Long Narrow Perpendicular Buildings

Abstract: This paper presents wind tunnel measurements of pedestrian wind conditions in passages between various configurations of two long narrow perpendicular buildings in open country exposure. The investigated parameters are passage width, building height and wind direction. The measurements were made along the passage centerline. The aim of the paper is to provide more insight in the pedestrian wind conditions in these basic building configurations, to address some contradictory statements reported in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 12 publications
6
80
0
2
Order By: Relevance
“…at the building position but without the building present, using a hot-film probe. Measuring at the turntable position yields the incident profiles for CFD simulation, which is very important for a reliable validation study [102,103]. A reference mean wind speed U ref = 6.97 m/s and a reference turbulence intensity of 10% were measured at building height.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…at the building position but without the building present, using a hot-film probe. Measuring at the turntable position yields the incident profiles for CFD simulation, which is very important for a reliable validation study [102,103]. A reference mean wind speed U ref = 6.97 m/s and a reference turbulence intensity of 10% were measured at building height.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…Blocken et al [4] configured two long and narrow buildings into diverging and converging types; in the wind tunnel testing, they simulated the open terrain wind speed profile to understand the wind passage. The results showed that the wind speed of the diverging passage was higher than that of the converging passage and that the wind speed increased with increasing street canyon width.…”
Section: Introductionmentioning
confidence: 99%
“…This is logical considering the definition of the nearest obstacle (section 3.5). However, this definition can be contested by the studies of Blocken et al [28] and Blocken et al [43], who show that the influence of smaller buildings can actually increase WDR on higher buildings, which is not accounted for in the Norm used as the reference model for this study. On the other hand, the presence of eaves and the height of the building do not reveal a pattern of WDR catch ratios.…”
Section: Resultsmentioning
confidence: 59%
“…10). This point was debated by Blocken et al [27] and Blocken et al [43] but more studies seem necessary to optimize obstruction factor definition in the Norm. Note that trees and buildings are treated the same way in terms of obstruction factor.…”
Section: S Coutu Et Al / Building and Environment XXXmentioning
confidence: 99%